(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Body Mass Index (BMI) is an easy-to-use method to assess the proportion between body weight and height, and is often used to detect potential risks of health problems. Observations on students revealed BMI discrepancies that are thought to be influenced by a sedentary lifestyle, lack of physical activity, and lifestyle patterns and academic pressures that do not support fitness. The purpose of this study was to identify the characteristics of Body Mass Index (BMI) in students of the Physical Education Study Program, FKIP, Tanjungpura University. In this study, the researcher applied a quantitative descriptive approach by utilizing a survey method. The population used was 76 Physical Education students of FKIP, Tanjungpura University who were 4th semester students. This study used a total sampling technique for sampling. The results of the study on the status of Body Mass Index of students of the Physical Education Study Program, FKIP, Tanjungpura University, showed that there were 5 students (6.58%) who were included in the very thin category, 5 students (6.58%) in the thin category, 60 students (78.95%) were in the normal category, 4 students (6.26%) in the overweight category and 2 students (1.52%) in the obesity category. It was concluded that the Body Mass Index of Physical Education students was in the normal category.